2008
DOI: 10.1080/01443610802281682
|View full text |Cite
|
Sign up to set email alerts
|

Obstructed labour in Enugu, Nigeria

Abstract: Obstructed labour is an important cause of maternal death in developing countries. Obstructed labour also causes significant maternal morbidity mainly due to infection and hemorrhage and foetal death from asphyxia is also common. Objectives are to reduce maternal and newborn complications by early detection and rapid interventions and to reduce maternal and perinatal morbidity and mortality. This Hospital-based prospective cross-sectional study was conducted from June 2013 to June 2014 in Sylhet, MAG Osmani Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
26
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 8 publications
8
26
4
Order By: Relevance
“…The reported incidence of obstructed labour in this hospital was 3.2% [1] which is very much in line with reported incidences in Nigeria and other parts of the developing world [2][3][4][5][6]. Foeto-pelvic disproportion was the commonest cause in this centre and Foetal congenital anomaly as a cause of obstructed labour was only 1.5% of cases with Hydrocephalus been the commonest; but this is the first time that bilateral Hydronephrosis will be documented.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The reported incidence of obstructed labour in this hospital was 3.2% [1] which is very much in line with reported incidences in Nigeria and other parts of the developing world [2][3][4][5][6]. Foeto-pelvic disproportion was the commonest cause in this centre and Foetal congenital anomaly as a cause of obstructed labour was only 1.5% of cases with Hydrocephalus been the commonest; but this is the first time that bilateral Hydronephrosis will be documented.…”
Section: Discussionsupporting
confidence: 71%
“…Therefore a destructive operation such as Embryotomy (Evisceration) after Decapitation and or Cleidotomy would have been treatment of choice. Caesarean Section has often been the alternative in Centres where destructive operations are not in use or of limited experience though abdominal deliveries in such cases carries higher risk of post operative wound infection as high as 34.3% [1][2][3]. However, destructive operations poses a substantial risk to the Mother in terms of Genital Tract lacerations or injuries to surrounding structures such as bladder or lower gastro intestinal tract [1][2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in low-income countries have reported that the prevalence of OL is between 2-8% of all institutional deliveries [12,13]. This may underestimate maternal deaths due to obstructed labor because it is rarely documented as a primary cause of death rather classified as, rather classified as sepsis, ruptured uterus or hemorrhage rather than the underlying cause [14].…”
Section: Introductionmentioning
confidence: 99%